Studying strictly positive secure capacity in cognitive radio-based non-orthogonal multiple access - Chi-Bao Le; Dinh-Thuan Do (Bulletin of Electrical Engineering and Informatics, 2021)
This paper studies a downlink security-aware secure outage performance in the secondary network of cognitive radio-assisted non-orthogonal multiple access network (CR-NOMA). The multiple relay is employed to assist transmission from the secondary source to destinations. The security-aware performance is subject to constraints in fixed power allocation factor assigned to each secondary user. The security-aware secure performance is based on channel state information (CSI) at the physical layer in which an eavesdropper intends to steal information. According to the considered system, exact expressions of Strictly positive secure capacity (SPSC) are proved to analyze system in terms of secure performance. Finally, the secondary user secure problem is evaluated via Monte-Carlo simulation method. The main results indicate that the secure performance of proposed system can be improved significantly.